PENGARUH LAYANAN INFORMASI TEKNIK DISCOVERY LEARNING UNTUK MENINGKATKAN PEMAHAMAN TENTANG PERGAULAN BEBAS PADA PESERTA DIDIK SMAN 11 KOTA JAMBI - Shikin, Nurha; Rasimin, Rasimin; Harahap, Nur Hasanah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The aim of this research is to determine the significant influence of information services using discovery learning techniques to increase understanding of promiscuity among students at SMA N 11 Jambi City. This research is a type of Quasi Experimental research with a sample of 38 people with samples taken using simple random sampling. Data collection in this research used the Free Association questionnaire instrument with a total of 30 items. The data analysis technique uses the C formula percentage calculation, normality test and t-test. The research results showed that students' understanding of free association before being given pretest treatment was 87% with a frequency of 33 in the medium category. Meanwhile, the level of understanding of students' free association after being given posttest treatment was 92% with a frequency of 35 in the high category. The results of the t-test obtained obtained a t-count value of -11.483, the significance value of Sig. (2-tailed) 0.000 < 0.05 which indicates Ha is accepted. So the hypothesis is stated that there is an influence between the pretest and posttest. It is recommended that guidance and counseling teachers pay more attention to students' interactions and apply information services using discovery learning techniques according to students' needs.